EL COJÍN NEUMÁTICO COMO UNA EXPERIENCIA DE LABORATORIO - Greis Julieth Cruz Reyes (Universidad Distrital Francisco José de Caldas, 2010)
Describes the construction of an air cushion table with a working guide that encourages the development of certain thinking skills which allow greater depth in the concepts through which mental models are descriptions own simulations based on different physical phenomena , this assembly creates a cushion of air that results in movement without friction, magnets on the surface chips off the table. The work guides give the guidelines leading to analyze simulations of physical phenomena where the dissipative factors can be considered approximately zero. The present article describes the construction of the air cushion and some applications to the introduction of concepts such as, gas pressure, relationship pressure volume and random motion of particles.